2014
DOI: 10.1186/s12995-014-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Job-related stress and work ability of dispatchers in a metropolitan fire department

Abstract: Background: Our aim was to assess psychomental stress and strain among dispatchers in fire departments, particularly during emergency instructions by phone and to evaluate their work ability. Methods: 27 dispatchers and 20 controls were examined. In a protocol, participants recorded 1. phone instructions causing mental stress (event) 2. working time without phone instructions (non-event) 3. breaks. Continuous heart rate (variability), urine catecholamine, salivary cortisol and lymphocytes were measured. To ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…Six articles assessed HRV during procedures such as intubations and lumbar punctures, and eight articles measured HRV during emergencies encountered during a shift. Of these 17 articles that were reviewed, eight reported statistically significant changes in HRV from baseline when participants were responding to medical emergencies [1,2,[4][5][6]13,17,18]. Although they did not all show statistically significant differences, all the studies reviewed showed that HRV metrics (SDNN, RMSSD, PNN50, LF%, and LF/HF) responded to the stress of a medical emergency in a similar way.…”
Section: Figure 1: Summary Of Search Results From the Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles assessed HRV during procedures such as intubations and lumbar punctures, and eight articles measured HRV during emergencies encountered during a shift. Of these 17 articles that were reviewed, eight reported statistically significant changes in HRV from baseline when participants were responding to medical emergencies [1,2,[4][5][6]13,17,18]. Although they did not all show statistically significant differences, all the studies reviewed showed that HRV metrics (SDNN, RMSSD, PNN50, LF%, and LF/HF) responded to the stress of a medical emergency in a similar way.…”
Section: Figure 1: Summary Of Search Results From the Search Strategymentioning
confidence: 99%
“…The field of medicine is filled with challenging situations and critical decisions that must be made rapidly, often by medical personnel fatigued or emotionally stressed. When responding to an emergency, many factors contribute to well-studied physiological stress responses including increased serum cortisol, blood pressure elevation, and elevated heart rate [1][2][3][4][5][6]. The State-Trait Anxiety Inventory (STAI) score represents a subjective interpretation of stress experienced but fails to capture physiological changes related to stress.…”
Section: Introductionmentioning
confidence: 99%
“…Although alarm operators are often seen as less vulnerable to critical events than paramedics, they reported experiencing disturbance with such calls [ 6 , 8 , 10 , 14 , 48 ], especially those concerning child sexual abuse, rape, and threats to a child’s life. The work-related stress for this type of work [ 6 , 12 , 19 , 23 , 25 , 34 , 53 ] is higher than in the general population and may be a risk factor for physical (e.g., sleeping difficulties, and hyperarousal) and mental (e.g., burnout, and emotional exhaustion) health-related conditions that typically coexist with PTSD. The link between injury symptoms and work-related stress has also been confirmed [ 20 , 21 ], so PTSD can be the consequence of permanent work-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Demands depending on the characteristics of the work may lead to physical, social, or organizational effort. For this reason, professions that require permanent mental and physical strain lead to real physical and emotional costs for employees [ 34 , 35 ]. Many known factors coexist with PTSD in frontline workers.…”
Section: Introductionmentioning
confidence: 99%
“…Role ambiguity and conflict contribute to adverse RS whereas workload may be a constructive stressor until stress levels exceed the coping skills and resources available to the employee (Crawford et al, 2010;Jamal, 1984Jamal, , 1985Newton and Teo, 2014;Schaufeli and Bakker, 2004;Singh et al, 1994) The general view that high levels of RS is detrimental to individuals and organizations has been widely supported and the subject of over 300 journal articles (Ortqvist and Wincent, 2006). Organizational and individual problems associated with RS include absenteeism (Goetzel et al, 1998); turnover (Mann, 1996); burnout (Holloway and Wallinga, 1990); emotional exhaustion (Posig and Kickul, 2003); deteriorating personal health (Cooper et al, 2001); job dissatisfaction (Cervoni and DeLucia-Waack, 2011); reduced organizational commitment ( Johnston et al, 1990); and lower performance 688 PR 45,4 (Abramis, 1994;Babin and Boles, 1996a, b;Lindegård et al, 2014;Oldenburg et al, 2014;Rebele and Micheals, 1990).…”
Section: Rs Definition Prevalence and Impactmentioning
confidence: 99%